The relationship between regional development, human development and poverty: A perspective from the Indonesian province - Machmud, Senen; Sidharta, Iwan (Nurture, 2023)
Purpose: This study investigates the relationship between human development, poverty and regional economic growth. There is short-run and long-run equilibrium. Design/Methodology/Approach: This research uses a quantitative approach with panel data from the Jambi Province National Bureau of Statistics for 2010-2022. Researchers used cointegration and Fully Modified Least Squares (FMOLS) panels to analyze research data. Findings: The results of the study indicate that human development has a positive and significant effect on gross domestic product growth but poverty has no effect on gross domestic product growth. The results of the coefficient calculation show a negative value indicating that an increase in gross domestic product growth can reduce poverty. Conclusion: The calculation results show the research model’s short-run and long-run relationships. Each aspect of HDI has a significant effect on GRDP. Therefore, if there is an increase in HDI, it will cause an increase in GRDP. Research Limitations and Implications: This study only uses human development and poverty variables. Future researchers should add variables that affect the region’s economic growth such as unemployment, inflation, welfare, regional inequality and developing countries. Practical Implications: The research results contribute to the recommendations of policymakers for the need to form a regional poverty reduction committee and develop regional poverty reduction strategies as the basis for mainstreaming poverty reduction, improving access and providing social service facilities such as education and health to reduce poverty and improve the welfare of Indonesian residents. Contribution to Literature: This research can add to the literature on regional economic growth, human development and poverty regarding macroeconomic studies’ short-run and long-run equilibrium.